Studi Deskriptif Tentang Praktik Penyusunan Anggaran Biaya Overhead Pabrik Pada Pt. Osaka Engineeringprima - Mellyyanah Wardiatul Janah; M Rifki Bastian; Septian Umar Rizqi; Addina Khairi Abdillah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine and describe the practice of preparing factory overhead cost budgets at PT. Osaka Engineering Prima, a manufacturing company engaged in engineering services. Factory overhead costs are a crucial component in the production cost structure, being indirect yet significantly influencing operational efficiency and the accuracy of cost of goods sold calculations. This research employs a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews, field observations, and internal company documentation. The results show that the budgeting process for factory overhead costs at PT. Osaka Engineering Prima is carried out systematically, involving relevant departments and considering both historical data and projected operational needs. However, challenges remain, particularly in budget control and the suboptimal use of information technology. This study recommends strengthening cost management systems and improving interdepartmental coordination to support greater efficiency and effectiveness in the preparation and control of factory overhead budgets.